Relevansi Tafsir Kata Māl Dengan Keadilan Sosial: Pendekatan Hermeneutika Hasan Hanafi - Habiburrahman, Habiburrahman (Indonesian Journal of Religion and Society, 2024)
The Qurʼān affirms the principle of social justice in the form of the phrase that the control of camels and horses from the spoils of war is under the control of Allah and the Messenger, his relatives, orphans, the poor and travellers. The mention of orphans and travellers, who are generally known to be propertyless people, is understood as Allah's way of making property or assets in modern terms circulate only among the rich. This article explains the hermeneutics of the word Māl and its relevance to social justice. This library research is a descriptive-analysis of the interpretation of Māl. The primary data are the Qurʼān and Hassan Hanafi's book. Secondary data are social justice literature and research on Hassan Hanafi's hermeneutics. Hassan Hanafi interprets the term Māl in terms that wealth is actually a trust, an alliance, a way of planting goodness (investment), and prohibits people from misusing it. The word māl has a strong relevance to the values of social justice. In the ideology of Pancasila, the goal of social justice is a social/state order that is balanced, organised, dignified and helps the weak. And it prohibits things that are detrimental to the common good, practices that benefit the few and harm the many.